METHODS OF TECHNOLOGICAL MACHINERY MONITORING AND FAULT DIAGNOSIS (Intent Research Scientific Journal, 2023)
The continuous advancement of technological machinery in various industries necessitates effective monitoring and fault diagnosis methodologies to ensure optimal performance and minimize downtime. This paper explores diverse methods employed in the field of technological machinery monitoring and fault diagnosis, aiming to enhance reliability and efficiency.